Unhoused Persons: Perspectives on Perceived Benefits of Music Therapy. Issue 1 (20th December 2021) - Lahue, Katie
Abstract: There is limited literature to support the use of music therapy with unhoused persons and more research is needed to deepen the understanding of music therapy with this population. This researcher aimed to gather information from music therapists who work with unhoused persons to gain more perspective on the perceived benefits of the music therapy treatment process. Three music therapists were interviewed; interviews were then transcribed and coded to find themes regarding perceived benefits of music therapy with unhoused persons. The four themes derived from the data were increased resilience factors, facilitating connections, creating a safe space, and increased expression. Findings support music therapy attending to many levels of human need for unhoused individuals. These findings can be used as recommendation for practice and program development for the use of music therapy with unhoused persons and also point to a need for more research to understand the benefits of specific music therapy techniques and treatment methods with unhoused persons and subgroups of the unhoused community.